2010
DOI: 10.1111/j.1748-3743.2010.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Restraints or alternatives: safety work in care of older persons

Abstract: The study has identified a process of 'safety work' that identified the risk associated with the problem, the work to cope with the problem and risk, the conditions that influenced the process and the consequences or outcomes of the work strategies to maintain the older person's safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The review yielded 23 articles that represented one mixed methods (Strumpf & Evans, ), seven quantitative (Farina‐Lopez, Estevez‐Guerra, Polo‐Luque, Pogranyiva, & Penelo, ; Janelli, Stamps, & Delles, ; Liukkonen & Laitinen, ; McCabe, Alvarez, McNulty, & Fitzpatrick, ; Myers, Nikoletti, & Hill, ; Suen et al, ; Werner, ) and 15 qualitative studies (Bok, Pierce, Gies, & Steiner, ; Boltz, Capezuti, & Shabbat, ; Brown, Williams, Woodby, Davis, & Allman, ; Chuang & Huang, ; Dahlke, Hall, & Baumbusch, ; Dahlke & Phinney, ; Goethals, Dierckx de Casterlé, & Gastmans, ; King, Pecanac, Krupp, Liebzeit, & Mahoney, ; Kneafsey, Clifford, & Greenfield, ; Lai, ; Lee, Chan, Tam, & Yeung, ; Ludwick, O'Toole, & Meehan, ; Nolan, ; Quinn, ; Schofield, Tolson, & Fleming, ). Nine were conducted in the United States, three in the United Kingdom, three in Hong Kong, two in Canada and one each in Spain, Taiwan, Belgium, Finland, Australia and Israel.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The review yielded 23 articles that represented one mixed methods (Strumpf & Evans, ), seven quantitative (Farina‐Lopez, Estevez‐Guerra, Polo‐Luque, Pogranyiva, & Penelo, ; Janelli, Stamps, & Delles, ; Liukkonen & Laitinen, ; McCabe, Alvarez, McNulty, & Fitzpatrick, ; Myers, Nikoletti, & Hill, ; Suen et al, ; Werner, ) and 15 qualitative studies (Bok, Pierce, Gies, & Steiner, ; Boltz, Capezuti, & Shabbat, ; Brown, Williams, Woodby, Davis, & Allman, ; Chuang & Huang, ; Dahlke, Hall, & Baumbusch, ; Dahlke & Phinney, ; Goethals, Dierckx de Casterlé, & Gastmans, ; King, Pecanac, Krupp, Liebzeit, & Mahoney, ; Kneafsey, Clifford, & Greenfield, ; Lai, ; Lee, Chan, Tam, & Yeung, ; Ludwick, O'Toole, & Meehan, ; Nolan, ; Quinn, ; Schofield, Tolson, & Fleming, ). Nine were conducted in the United States, three in the United Kingdom, three in Hong Kong, two in Canada and one each in Spain, Taiwan, Belgium, Finland, Australia and Israel.…”
Section: Resultsmentioning
confidence: 99%
“…In 2 of the studies, nursing staff in the United States (US) (Janelli et al, ) and the United Kingdom (UK) (Schofield et al, ) discussed using chemical restraints to keep their older patients from harms that were defined as falling or removing medical equipment (e.g., catheters, intravenous lines). Studies from Taiwan (Chuang & Huang, ), Spain (Farina‐Lopez et al, ), the United States (King et al, ; Ludwick et al, ; McCabe et al, ; Quinn, ; Strumpf & Evans, ), Hong Kong (Lai, ; Lee et al, ; Suen et al, ), Finland (Liukkonen & Laitinen, ), Australia (Myers et al, ) and Israel (Werner, ) all reported nurses' use of physical restraints to keep their older patients safe. Four of the studies identified that once physical restraints had been applied to an older patient, nursing teams were reticent to remove them, even if the reason for using the restraint was no longer present (Chuang & Huang, ; Goethals et al, ; Ludwick et al, ; Suen et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations